Application of an oral health-related quality of life questionnaire in primary care patients with orofacial pain and temporomandibular disorders - Blanco-Aguilera, Antonio (Medicina Oral S.L., 2014)
Objectives: To examine whether patients who report orofacial pain (OP) and temporomandibular disorders (TMD) have a poorer perception of their oral health-related quality of life and, if so, to what extent, and to analyze the association between oral health perception, sociodemographic variables and reported pain duration. Study Design: 407 patients treated at the OP and TMD units in the Healthcare District of Cordoba, Spain, diagnosed following the standard criteria accepted by the scientific community – the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) – were administered the Spanish version of the Oral Health Impact Profile questionnaire (OHIP-14). Bivariate and logistic regression analyses were performed to determine the degree of association between the patients’ OHIP-14 score and pain duration, pain intensity, and various sociodemographic variables. Results: The observed distribution was 89.4% women and 10.6% men. The mean OHIP-14 score was 20.57 ± 10.73 (mean ± standard deviation). A significant association (p<0.05) was found for gender, age, marital status, chronic pain grade, self-perceived oral health status and pain duration. Conclusions: The analysis of self-perceived oral health status in patients with OP and TMD, as measured by the OHIP-14, showed that oral health is perceived more negatively by women. Moreover, a one-point increase in the Chronic Pain Grade indicator increases the OHIP-14 indicator by 4.6 points, while chronic pain, defined as pain suffered by patients for one year or more, increases the OHIP-14 indicator by 3.2 points.